A new species and additional records of the microphthalmous Lathrobium species of Turkey (Coleoptera: Staphylinidae: Paederinae) - Anlaş Si̇nan (Zootaxa, 2018)
A new species of microphthalmous Lathrobium Gravenhorst from Yozgat province in central northern Anatolia is described and its diagnostic characters are illustrated: Lathrobium newtoni sp. n. Additional records of four microphthalmous Lathrobium species are reported. A key to the microphthalmous Lathrobium species of Turkey is presented. Distributions of microphthalmous Lathrobium species in Anatolia are mapped.